(untitled) (Research, Society and Development, 2020)
This research aimed to estimate the prevalence of stress factors related to time management in university students, as well as to investigate possible factors associated in this relationship. This is an associative cross-sectional study, conducted in a sample of 303 participants, the outcome variable was the simultaneous presence of stressful factors related to time management and as predictors of sociodemographic variables. In the sociodemographic profile, it is highlighted that the majority of students were female 71.0%, aged under 25 years old (79.0%) and without working (63.0%). Among the stressor, the prevalence of lack of time for leisure activities was (66.0%) and the difficulty in time management (57.0%). The multiple stressors as an outcome variable were evidenced by 59.0% of the interviewed students. Regarding the lifestyle analysis as independent variables (predictors), show that 47.0% reported alcoholic consuming. After crude and adjusted analysis, working students were more likely to be exposed to multiple stressors. The increase in the level of stress of university students is related to time management to reconcile academic activities and other social, emotional, family, and personal demands, factors that enhance when the student works and studies. The need for a global intervention by universities is emphasized, to protect the students’ mental health.